1958
DOI: 10.1590/s0006-87051958000100003
|View full text |Cite
|
Sign up to set email alerts
|

Alguns estudos preliminares sôbre possíveis problemas de fertilidade, em solos de diferentes campos cerrados de São Paulo e Goiás

Abstract: Êste trabalho representa uma primeira contribuição para o estudo da fertilidade dos solos de campos cerrados. Tais solos, que ocupam importante superfície do território nacional, apresentam muitas vezes boas propriedades físicas e regulares disponibilidades de água, que parecem estar em desacôrdo com a pobreza da vegetação nêles desenvolvida. Uma deficiência ou um agudo desequilíbrio de nutrientes deve, pois, estar envolvido. De fato, a cultura em vasos permitiu verificar uma acentuada deficiência em fósforo n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

1959
1959
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Data on possible soil fertility problems of several campos of the States of Sao Paulo and Goias were reported recently (McClung, et al 1957). These results, obtained from greenhouse pot culture studies, suggested that acute phosphorus deficiency might be the most important fertility problem common to the six soils studied.…”
Section: Sulfur Deficiency In Soils From Brazilian Camposmentioning
confidence: 99%
“…Data on possible soil fertility problems of several campos of the States of Sao Paulo and Goias were reported recently (McClung, et al 1957). These results, obtained from greenhouse pot culture studies, suggested that acute phosphorus deficiency might be the most important fertility problem common to the six soils studied.…”
Section: Sulfur Deficiency In Soils From Brazilian Camposmentioning
confidence: 99%
“…As limitações que a falta de S pode ocasionar na produção vegetal em solos brasileiros não é fato recente. Já no final da década de 50, vários trabalhos (McClung et al, 1958(McClung et al, , 1961McClung & Freitas, 1959) evidenciavam a baixa capacidade desses solos em suprir as necessidades de S devido aos seus baixos teores de matéria orgânica, uma vez que aproximadamente 90% do S do solo encontra-se na forma orgânica (Wolffenbüttel & Tedesco, 1981).…”
Section: Introductionunclassified
“…In the cerrado region the presence of typical cerrado species in the vegetation bordering the rivers, the gallery forest, is very rare (Eiten 1972, Felippe & Dale 1990. Cerrado soil is very poor in nutrients like P, N, S, Ca, Mo and B but the aluminium availability is very high (Arens 1958, McClung et al 1958, Alvim et al 1968, Reatto et al 1998.…”
mentioning
confidence: 99%